Investigation on Potential of Karanjin Loaded Emulgel for Improved Efficacy against Psoriasis - Desai, Jagruti; Patel, Riddhi; Desai, Dhvani (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim: The objective of this work was to prepare and characterize Karanjin loaded emulgel for enhanced effectiveness against psoriasis. Materials and Methods: Karanjin emulsion was prepared using peppermint oil and was loaded in gel base (carbopol 940 was used as gelling agent). Various batches of emulsion were prepared by varying concentration of tween 80 and were optimized for various parameters. Results: Optimized emulsion (KE5) gave droplet size of 110.4 ± 1.56 nm, -40.9 ± 1.11 mV zeta potential, entrapment efficiency of 92.12 ± 2.8%, and creaming volume of 98.1 ± 0.4 and was found to be stable for 30 days during short term stability studies. The pH and viscosity of optimized Karanjin loaded emulgel was found to be 7.31 and 8060 cp respectively. In-vitro release of Karanjin from optimized emulgel was found to be 95.36% in 6 hr indicating slow release. Ex vivo permeation study in skin indicated 88% permeation of karanjin in 5 hr from optimized emulgel formulation compared to 16.52% permeation from solution formulation. In vivo study showed significant improvement in PASI score upon application of Karanjin loaded emulgel formulation. Conclusion: The results prove potential efficacy of the emulgel formulation in improving efficacy of Karanjin against psoriasis.
Keywords: Psoriasis; Emulgel; Karanjin; PASI Scoring; In vivo anti-psoriatic activity; Ex vivo permeation